2012
DOI: 10.1093/nar/gks868
|View full text |Cite|
|
Sign up to set email alerts
|

SPOC1 modulates DNA repair by regulating key determinants of chromatin compaction and DNA damage response

Abstract: Survival time-associated plant homeodomain (PHD) finger protein in Ovarian Cancer 1 (SPOC1, also known as PHF13) is known to modulate chromatin structure and is essential for testicular stem-cell differentiation. Here we show that SPOC1 is recruited to DNA double-strand breaks (DSBs) in an ATM-dependent manner. Moreover, SPOC1 localizes at endogenous repair foci, including OPT domains and accumulates at large DSB repair foci characteristic for delayed repair at heterochromatic sites. SPOC1 depletion enhances t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 75 publications
4
69
0
Order By: Relevance
“…Primary antibodies specific for the viral proteins used in this study included E1A mouse monoclonal antibody (MAb) M73 (35), E1B-55K mouse MAb 2A6 (36), E2A-72K mouse MAb B6-8 (37), E4orf6 mouse MAb RSA3 (38), L4-100K rat MAb 6B-10 (39), E4orf3 rat MAb 6A11 (40), and HAdV type 5 (HAdV5) rabbit polyclonal serum L133 (34). Primary antibodies specific for cellular proteins included KAP1 rabbit polyclonal antibody H-300 (Santa Cruz Biotechnology), phospho-KAP1 (S824) rabbit polyclonal antibody (Bethyl Laboratories, Inc.), SPOC1 rat monoclonal antibody 6F6 (8,10), GAPDH 2542 KAP1S824A fwd 5=-CTGGCCTGAGTGCCCAGGAGCTG-3= 2543 KAP1S824A rev 5=-CAGCTCCTGGGCACTCAGGCCAG-3= 2548 KAP1K554A fwd 5=-GTCTCCTCCTCCGCGACAATGG-3= 2549 KAP1K554A rev 5=-CCATTGTCGCGGAGGAGGAGAC-3= 2550 KAP1K779A fwd 5=-TGCACGTCTGCCGCGTCCTCAG-3= 2551 KAP1K779A rev 5=-CTGAGGACGCGGCAGACGTGCA-3= 2552 KAP1K804A fwd 5=-ACAGCAGAGAACGCGGTGTCACC-3= 2553 KAP1K804A rev 5=-GGTGACACCGCGTTCTCTGCTGT-3= 2645 KAP1K676A fwd 5=-CATCCTCCTCCGCCAGGTCAGG-3= 2646 KAP1K676A rev 5=-CCTGACCTGGCGGAGGAGGATG-3=…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary antibodies specific for the viral proteins used in this study included E1A mouse monoclonal antibody (MAb) M73 (35), E1B-55K mouse MAb 2A6 (36), E2A-72K mouse MAb B6-8 (37), E4orf6 mouse MAb RSA3 (38), L4-100K rat MAb 6B-10 (39), E4orf3 rat MAb 6A11 (40), and HAdV type 5 (HAdV5) rabbit polyclonal serum L133 (34). Primary antibodies specific for cellular proteins included KAP1 rabbit polyclonal antibody H-300 (Santa Cruz Biotechnology), phospho-KAP1 (S824) rabbit polyclonal antibody (Bethyl Laboratories, Inc.), SPOC1 rat monoclonal antibody 6F6 (8,10), GAPDH 2542 KAP1S824A fwd 5=-CTGGCCTGAGTGCCCAGGAGCTG-3= 2543 KAP1S824A rev 5=-CAGCTCCTGGGCACTCAGGCCAG-3= 2548 KAP1K554A fwd 5=-GTCTCCTCCTCCGCGACAATGG-3= 2549 KAP1K554A rev 5=-CCATTGTCGCGGAGGAGGAGAC-3= 2550 KAP1K779A fwd 5=-TGCACGTCTGCCGCGTCCTCAG-3= 2551 KAP1K779A rev 5=-CTGAGGACGCGGCAGACGTGCA-3= 2552 KAP1K804A fwd 5=-ACAGCAGAGAACGCGGTGTCACC-3= 2553 KAP1K804A rev 5=-GGTGACACCGCGTTCTCTGCTGT-3= 2645 KAP1K676A fwd 5=-CATCCTCCTCCGCCAGGTCAGG-3= 2646 KAP1K676A rev 5=-CCTGACCTGGCGGAGGAGGATG-3=…”
Section: Methodsmentioning
confidence: 99%
“…Another well-studied SPOC1-interacting protein is the hetero-chromatin-associated transcription factor KAP1 (Kruppel-associated box [KRAB]-associated protein 1)/transcriptional intermediary factor 1␤ (TIF1␤)/KRAB-interacting protein 1 (KRIP1)/ tripartite motif containing 28 (TRIM28) (9,10). Recruitment of this protein to genetic loci increases H3K9me2/3 repressive histone marks, induces the formation of heterochromatin, and blocks gene expression (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H3K9me2 can also be associated with openness/ gene activity when present at the 5' region of a gene 47 and can reflect changes elicited by DNA damage responses. 48,49 p53 and ER have been functionally and physically related to proteins involved in chromatin methyl mark changes, such as G9a and LSD1. [50][51][52][53][54][55] However, the outcome of the induced epigenetic changes is variable.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, PHF13 has been previously shown to play a role in DNA damage response (DDR) and DNA repair and likewise to interact with several proteins important for DNA repair and surveillance. 26 One such factor, TRIM28 (also known as TIF1b and KAP1), has been recently shown to globally regulate RNAPII promoter proximal pausing and release, which hinged on whether or not it was phosphorylated by DNA-PK and ATM, two important DDR kinases. 27,28 PHF13 interacts with all of these proteins to modulate DDR, and we have recently shown that in the absence of induced DNA damage (albeit DNA damage and recovery is a continuous and naturally occurring process, even in the absence of DNA damage inducing agents) PHF13 interacts with TRIM28 and ATM.…”
Section: Promoter/promoter Proximal Pausingmentioning
confidence: 99%